COVID-19: the difference between the nose and the lung - Gelardi, Matteo; Notargiacomo, Mario; Trecca, Eleonora Maria Consiglia; Cassano, Michele; Ciprandi, Giorgio (Monaldi Archives for Chest Disease, 2021)
To the Editor An elegant study reported dysmorphic cells and syncytia in the deceased’s lungs for COVID-19. The authors reasonably considered that most of these syncytia-forming cells were pneumocytes, as identified by specific biomarkers. However, cellular dysmorphism and syncytia are pathological features common in other respiratory infections caused by different viruses, including the human respiratory syncytial virus (HRSV) and Epstein-Barr virus (EBV), as correctly documented...